Penerapan Asas-Asas Umum Pemerintahan Yang Baik Dalam Praktik Peradilan Di Indonesia - Sri Nurhari Susanto (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2021)
Abstract Legal protection for the people is not only found in written legal provisions, but also in unwritten laws which in Administrative Law are commonly referred to as General Principles of Good Administration ((in Indonesia it is called AUPB). Recognition of AUPB as part of the legal norms of government and norms of legal protection for citizens is a consequence of the development of the rule of law concept. AUPB thus no longer merely acts as a legal principle in general, but turns into a legal norm that is formulated into law or made by judges through their decisions in resolving administrative disputes. Consistency and seriousness of judges in formulating legal facts, compiling legal considerations in order to identify and formulate AUPB is very much needed in practice. The way judges relate and interpret the indicators in each AUPB in each of their decisions, starting from the examination of the case to making a decision, is carried out at least through 3 stages, namely the stage of collecting facts, the stage of identifying the law, and the stage of formulating the law and the AUPB. Keywords: Administrative Dispute, General Principles of Good Administration (AUPB), Judicial Practice. AbstrakPerlindungan hukum bagi rakyat tidak hanya terdapat pada ketentuan hukum tertulis saja, tetapi juga terdapat pada hukum tidak tertulis yang dalam Hukum Administrasi lazim dikatatan sebagai Asas-Asas Umum Pemerintahan yang Baik (AUPB). Pengakuan terahadap AUPB sebagai bagian dari norma hukum pemerintahan dan norma perlindungan hukum bagi warga merupakan konsekuensi dari berkembangnya konsep negara hukum. AUPB dengan demikian tidak lagi sekedar berperan sebagai asas hukum pada umumnya, tetapi berubah menjadi norma hukum yang dirumuskan ke dalam undang-undang maupun dibuat oleh hakim melalui putusan-putusannya dalam menyelesaikan sengketa administrasi (sengketa TUN). Konsistensi dan kesungguhan hakim dalam merumuskan fakta-fakta hukum, menyusun pertimbangan hukum guna mengidentifikasi dan merumuskan AUPB sangat diperlukan dalam praktik. Cara hakim dalam menghubungkan dan memaknai indikator pada masing-masing AUPB dalam setiap putusannya, maka diawali dari pemeriksaan perkara sampai pada pe-ngambilan keputusan paling tidak dilakukan melalui 3 tahapan, yaitu tahap pengumpulan fakta, tahap mengidentifikasi hukum, dan tahap merumuskan hukum dan AUPB.Kata Kunci : Sengketa TUN, Asas-Asas Umum Pemerintahan yang Baik (AUPB), Praktik Peradilan.